The Social Impact of the Kafala System Reform on Female Migrant Workers (TKW) and the Dynamics of Bilateral Politics between Indonesia and Saudi Arabia - Rivandha, Razzaqitaqwa; Solihat, Ade (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The kafala system had long been the main mechanism for managing migrant workers in Saudi Arabia, but it was often criticized for creating excessive dependency between workers and employers, which led to exploitation. Kafala reform was an important step to improve the protection and welfare of Indonesian female migrant workers, especially because the majority were employed in the domestic sector that was highly vulnerable to violence, wage theft, and restricted mobility. In this context, the bilateral relations between Indonesia and Saudi Arabia played a strategic role in ensuring the implementation of fairer policies for female migrant workers. This study aimed to analyze the impact of kafala reform on the protection of Indonesian female migrant workers and to evaluate the role of bilateral diplomacy in supporting the reform. A qualitative descriptive-analytical approach was applied, using document analysis of regulations, reports from international organizations, official BP2MI data, and media publications. The data were analyzed through thematic analysis, policy analysis, and source triangulation to increase the validity of the findings. The results showed that kafala reforms, including the abolition of exit permits, job mobility, and the introduction of digital contracts, had a positive impact on improving mobility and legal certainty for female migrant workers. However, weak supervision, cultural resistance from employers, and limited access to complaint mechanisms remained major obstacles. Bilateral diplomacy through Memoranda of Understanding (MoU) played an important role, but protection still focused on the formal sector. Therefore, this study recommended strengthening the implementation of reforms, expanding protection to the domestic sector, integrating inter-agency data, and enhancing bilateral and multilateral cooperation to ensure sustainable protection of Indonesian female migrant workers.